Maternal feeding practices and children's food intake during an ad libitum buffet meal: Results from the GUSTO cohort. (1st November 2019) - Fries, Lisa R.; Chan, Mei Jun; Quah, Phaik Ling; Toh, Jia Ying; Fogel, Anna; Goh, Ai Ting; Aris, Izzuddin M.; Broekman, Birit F.P.; Cai, Shirong; Tint, Mya Thway; Chong, Yap Seng; Shek, Lynette P.; et al.
Abstract: Parents' feeding practices have been shown to be associated with children's food intake and weight status, but little is known about feeding practices in Asian countries. This study used behavioral observation to explore the feeding practices of 201 mothers of 4.5 year-old children in Singapore during an ad libitum buffet lunch. Feeding practices were coded from videos, focusing on behaviors used to prompt the child to eat more food (autonomy-supportive and coercive-controlling prompts to eat, suggesting items from buffet), those to reduce intake (restriction, questioning food choice), and those related to eating rate (hurrying or slowing child eating). Child outcome measures included energy consumed, variety of food items selected, and BMI. Maternal restriction and trying to slow child eating rate were associated with higher energy consumed by the child ( r  = 0.19 and 0.13, respectively; p < 0.05). Maternal autonomy-supportive prompts and restriction were associated with a greater variety of items selected by children ( r  = 0.19 and 0.15, respectively; p < 0.05). The frequency of maternal feeding practice use differed across ethnic groups, with Malay mothers using the most prompts to eat (p < 0.05), Chinese mothers most likely to question a child's food choice (p < 0.01), and Indian mothers the last likely to tell the child to eat faster (p < 0.001). There were no differences between ethnic groups for other feeding practices. No associations were found between feeding practices and child BMI. It is possible that feeding practices related to restriction and slowing child eating are adopted in response to children who consume larger portions, although longitudinal or intervention studies are needed to confirm the direction of this relationship and create local recommendations.